Urban resilience based systems managment - DOWLING, CONOR MARK (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2020)
As a result of climate change cities face challenges of growing complexity and uncertainties including increasing magnitude and volume of droughts, storms and flooding among other extreme weather events. Traditional risk management, based on probabilistic quantitative methods, are no longer sufficient to address the unpredictability and magnitude of these events. These challenges are further complicated by the increased interdependency of many of society's urban systems which presents a fundamental challenge to even the most comprehensive risk analysis. In response to this problem urban resilience has grown in popularity as a way to address the impacts of climate change and to maintain the functionality of urban systems during disaster events. However urban resilience remains siloed in its application to either built infrastructure systems or the communities they support and there is a significant gap in the literature as to how these two resilience types can be brought together. The early integration of resilience into the design of critical infrastructure systems management is needed to complement the existing knowledge-base of risk analysis and to address the emerging issues associated with complexity and uncertainty. This thesis argues for the significance of resilience in urban development and the necessity for practitioners to engage with the emerging concept of viewing critical infrastructure as part of a wider complex socio-technical system (STS). The research aims to develop and trial professional approaches to embed resilience within design processes through an empirical contribution with the development of a Resilience Management Framework (RMF). This framework aims to provide decision makers with a baseline measurement of STS resilience and suggests how resilience capabilities may be improved. The framework is tested with a case study which helps to develop practical pathways to resilience attainment. This study is complemented by expert interviews which aim to elicit effective and practical approaches to the implementation of conditions for urban resilience. The study identified sources of resilience and resilience dynamics that require management in the context of STS management. The thesis is concluded with a discussion on the importance of new professional tools for facilitating the delivery of resilient systems and with the conclusions of the study.
Merging the concepts of community and infrastructure resilience
APPROVED
Keywords: Complex Systems; Indicators; Flooding; Climate Change; Geographic Information System; Urban resilience